Підготовка вчителів англійської мови в системі багаторівневої педагогічної освіти Канади: сучасні тенденції - Павлюк, Віктоія (Studies in Comparative Education, 2014)
У статті розглядаються сучасні тенденції підготовки вчителів англійської мови у Канаді, уточнено значення поняття «багаторівнева педагогічна освіта»; охарактеризовано підготовку фахівців за певними освітніми рівнями; виділено основні принципи модернізації професійної педагогічної освіти в Канаді; підкреслено роль реформування змісту підготовки майбутніх учителів у Канаді у ХХІ ст., яка поряд із врахуванням освітніх інновацій співвідноситься з освітніми вимогами, що ставляться канадською сучасністю перед педагогічними кадрами та визначені сучасні вимоги до педагогічної освіти і професії вчителя в Канаді. В статье рассматриваются современные тенденции подготовки учителей английского языка в Канаде, уточнено значение понятия «многоуровневое педагогическое образование»; охарактеризовано подготовку специалистов по определенным образовательным уровням; выделены основные принципы модернизации профессионального педагогического образования в Канаде; подчеркнута роль реформирования содержания подготовки будущих учителей в Канаде в XXI в., которая, с учетом образовательных инноваций, соотносится с образовательными требованиями, предъявляемым канадской современностью перед педагогическими кадрами и определены современные требования к педагогическому образованию и профессии учителя в Канаде. In the article modern tendencies of English teachers’ training of Canada are examined, the value of concept «multilevel pedagogical education» is specified; preparation of specialists is described after certain educational levels; basic principles of modernisation of trade pedagogical education in Canada are distinguished; the role of maintenance training reformation of future teachers in Canada in 20 th century is underlined, that is connected with an account of educational innovations and correlated with educational requirements which a contemporary Canadian society has got in terms of pedagogical shots and certain modern requirements to pedagogical education and teacher’s profession of in. The study of essence and analysis of modern approaches to the problem of teacher’s pedagogical mastery in the system of higher pedagogical education, ground to assert, that forming mastery work better due to multilevel organization of educational process. In this context a large value in relation to the professional training of competitive pedagogical staff in Ukraine acquires the study of functioning of the national systems of multilevel pedagogical education in different countries of the world. Thus, the special interest is in the context of foreign experience study, and in theoretical and practical analysis of multilevel teachers’ training problem in Canada. Canada as multinational country accumulates in itself experience different nations in relation to organization of educational process, maintenance and methods of studies, that attracted attention of both home and foreign researchers. Canada owns ponderable pedagogical achievements and developed system of professional teachers’ training. So, a study and analysis of Canadian teachers’ training experience are an important source for determination of strategic directions in development of Ukrainian pedagogical education in 21 th century.